Analisis utang luar negeri, sukuk, inflasi dan tingkat suku bunga terhadap pertumbuhan ekonomi indonesia Tahun 2014-2019 - Septiana Sari; Fernaldi Anggadha Ratno (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
The purpose of this study was to determine the effect of Foreign Debt (X1), Sukuk (X2), Inflation (X3) and Interest Rate (X4) on Economic Growth (Y). This type of research is quantitative research using regression analysis as data analysis and using secondary data in the form of time series. The data used are monthly data from Foreign Debt, Sukuk, Inflation and Interest Rates and Economic Growth in 2014-2019 Data that has been obtained 72 samples then analyzed using the application tool E-views 9. Based on the results of this study indicate that the partial dependent variable External Debt influences positively and insignificantly, Sukuk positively influences and insignificantly, Inflation influences positively and insignificantly and Interest Rates have a positive and insignificant effect on the independent variables Economic Growth shown through Gross Domestic Product (GDP ).